Usability study of a simplified electroencephalograph as a health-care system. Issue 1 (December 2015) - Motomura, Shinichi; Ohshima, Muneaki; Zhong, Ning
Abstract A healthy lifestyle is becoming increasingly important worldwide, and various health monitoring devices that support this trend are currently being developed. Devices measuring blood pressure, weight, temperature, and pulse have been mainstream. In contrast, electroencephalography has been only useful in medical practice and brain research. For an electroencephalograph to be used in health care, it must be small and user-friendly. The conventional electroencephalograph uses more than twelve electrodes attached to a user's head with paste and hence is very precise. In contrast, the simplified electroencephalograph has inferior precision, but it is cheap, lightweight, paste-free, and requires only a short setup time. In this study, we verified the usefulness of the simplified electroencephalograph in investigating the mental condition of persons. We present interesting results associated with the setting position of the electrodes, the behavior of brain waves during work, and the appearance of individual differences. Consequently, we predict that this simplified device will be widely used for health diagnosis.